The dynamics of auctions for social-interest properties in Rio de Janeiro: digital strategies, commercialization process, and territorial impacts - Martins, Júlia Saraiva Barbosa (Geografares, 2026)
Amid high real estate delinquency, especially in social housing, this article seeks to update indebtedness relevance by bringing attention to the role of digital platforms in the reorganization of the real estate auction market in the city of Rio de Janeiro. Based on netnography procedures, it was analyzed how the emerging platformization (Pessanha, 2020a) of real estate auctions, by accelerating the circulation of repossessed properties, consolidates a new circuit of real estate commercialization with potential implications for the production of urban space and the deepening of housing-related indebtedness.